SPATIAL VARIABILITY OF SORGHUM YIELD AND SOIL PROPERTIES IN THE REGION OF THE SAVANNA-WETLAND ECOTONE IN MATO GROSSO DO SUL, BRAZIL - Montanari, Rafael [UNESP] (2015)
Sorghum bicolor (L.) Moech is an important high production forage crop that is increasingly used in Brazil, though still slow in replacing growing of second crop maize. Growing sorghum during the dry season would be an alternative for silage production and its use in the rainy season. However, plant growth and development will be affected if alterations occur in the texture, porosity, and structure of the soil. The objective of this study was to analyze the spatial variability and linear correlation between forage sorghum yield and soil properties in the 2011/2012 crop year in an Albaqualf soil in the region of the savanna-wetland ecotone. Thus, we estimated the fresh matter yield and dry matter yield (FMY and DMY) of forage sorghum and soil properties such as macroporosity (Ma), microporosity (Mi), total porosity (Pt), geometric mean diameter, weighted mean diameter, aggregate stability index (ASI), and the total organic carbon (TOC) content at two depths: 1 (0.00-0.10 m) and 2 (0.10-0.20 m). Fifty collections of plant and soil properties were conducted in 40 ha to form a geostatistical grid. This made it possible to find high spatial variability of plant production (FMY and DMY) and also the observation of soil properties that are most varied spatially. Concerning the variables that showed spatial dependence, the coefficient of determination (r(2)) decreased in the following order: ASI1, silt2, Ma1, Pt1, sand2, silt1, DMY, clay1, FMY and ASI2. Thus, we found that ASI1 showed the best semivariogram fit (r(2) = 0.926), with a range of 677.0 m, and moderate evaluation of spatial dependence (50.6 %). Silt1, however, had the lowest range (111.0 m), and thus it is recommended that in future studies the minimum range to be adopted for this type of evaluation should not be less than this value in an Albaqualf under conventional tillage. Linear correlation was highly significant and high for FMY and DMY, whereas in the interaction plant production versus soil properties there were positive and negative correlations. Within cokriging, clay1 was the best indicator for estimating the spatial variability of dry matter yield of sorghum forage with a significant and negative (r = -0.292*) correlation.